Paying for convenience corruption and revenue spending in Hongkong - Faure, David (Philippine Journal of Public Administration, 1980)
A bribe may be paid to buy convenience in the area of revenue spending. It may be given to gain access to revenue and/or lift the control over revenue spending. As a form of corruption, its causes were examined in Hong Kong and it was found out to have resulted from the lack of enforcement and not from the shortage of rules. The actual spending of revenue follows rules and regulations given out by the Hong Kong government. These rules suffer from incompetence and carelessness, thus breeding opportunities for corruption to arise. These opportunities come to be exploited and results proved that corruption pays. To prevent this, the Hong Kong government uses three approaches: investigation and prosecution which yield little result; prevention whose major action is the establishment of the Independent Commission Against Corruption (ICAC) in 1974; and publicity programs which act as supplement. How- ever, these approaches suffered a major blow when the Governor declared an amnesty on acts of corruption committed before 1978. This implied that the government could not pursue the crime offenders because it could not afford to lose its own staff. Thus, importance should be placed now on strengthening public confidence - to prove that the government can and is willing to enforce its law.